Asuhan Kebidanan Komprehensif Pada Ny. ‘’W’’ G1P0A0 Dengan Penerapan Senam Nifas Di Klinik Bp Annisa Banyuasin - Ratna Dewi; Wahyu Ernawati; Siti Aisyah (Universitas Pahlawan Tuanku Tambusai, 2024)
Comprehensive midwifery care is midwifery care provided comprehensively which includes continuous examination activities, namely midwifery care in pregnancy, childbirth, postpartum and newborn babies. Pregnancy, childbirth, postpartum and newborn babies are physiological conditions, but in the process there is the possibility of a situation occurring that can threaten the lives of the mother and baby and can even cause death. Every pregnancy can pose a risk of maternal and fetal death, monitoring and adequate health care during pregnancy, labor, postpartum and newborns is very important for the survival of the mother and baby. The aim is to provide comprehensive midwifery care for Ny'W' by implementing postpartum exercises at the BP Annisa Banyuasin clinic. The research method is descriptive analytical research using cross sectional research in the form of a case study which was carried out in June 2024 at the BP Annisa Banyuasin clinic. The research subject was Ny'W' aged 28 years G1P0A0 starting from pregnancy, childbirth, postpartum and newborn. Data collection techniques include observation, interviews, physical examination, support and documentation using midwifery care format instruments, observation tools and documentation tools. The results of comprehensive midwifery care carried out on Ny'W' G1P0A0 were carried out from the third trimester of pregnancy, namely 37 weeks of gestation to 39 weeks 2 days of gestation, during the ANC examination there were no complaints and the pregnancy progressed normally. Diagnosis G1P0A0 term inpartum pregnancy in the 1st stage of active phase, live single fetus, cephalic presentation. Ny'S' labor took 8 hours in the first stage, 15 minutes in the second stage, 10 minutes in the third stage and 2 hours in the fourth stage and was normal and there were no problems. Care for newborns was carried out 3 times without any problems being found. Postpartum care was carried out 3 times by implementing postpartum exercises for 10 days and screening for early detection of post partum depression using the EPDS pre test and post test questionnaire. The EPDS results showed that there was a decrease in the EPDS questionnaire score results in post partum mothers, which means there was an influence on the prevention of post partum depression. . Conclusion: Comprehensive midwifery care for Ny'W' at the BP Annisa Banyuasin clinic has been implemented in accordance with midwifery care standards and no problems were found, there is a gap between theory and practice in midwifery care during pregnancy, childbirth and postpartum. The results of implementing postpartum exercise and early detection of post partum depression using the pre and post test EPDS questionnaire showed that there was a decrease in the EPDS questionnaire score results in post partum mothers, which means there is an influence on the prevention of post partum depression.